Islamic Conception in The Utilization of Cocoa Pulp Waste As Basic Ingredients of Vinegar - Hafsan Hafsan; Arifuddin Ahmad; Elkheir Hassaballah Abdallah (Quality Assurance Institute (LPM) State Islamic University Walisongo Semarang, 2021)
Vinegar is a liquid containing acetic acid from fruits or other agricultural products through a multistage fermentation process. Cocoa pulp liquid waste with high sugar content can be used as raw material for various products such as vinegar through a biotechnology approach. This process is one of the efforts to utilize and at the same time overcome environmental pollution by utilizing the services of microbes that produce acetic acid. In the context of the use of natural resources, including the use of waste, this is relevant to Allah's command so that humans can make practical use of all His blessings as stated in the Qur'an. On the other hand, as a food ingredient, vinegar has a critical halal point that needs to be reviewed based on the process. This review describes the production process of vinegar produced through the processing of cocoa pulp waste and an Islamic review of the product to follow the concept of food safety in Islam, namely halal and thayyib.